Empowering women with fetal malpositions: enhancing childbirth experience and empowerment through educational interventions: a randomized controlled clinical trial - Xiuhong Wang; Xueyan Wang; Xiaofeng Wan; Xueheng Wen; Cailing Lv; Jinguo Zhai (BMC Pregnancy and Childbirth)
Abstract Background This study aims to determine the impact of a childbirth educational intervention, based on empowerment theory, on childbirth experience and empowerment in women with fetal occiput posterior and occiput transverse malpositions. Methods A randomized controlled trial was conducted from February 2022 to December 2022 involving pregnant women with fetal occiput posterior and occiput transverse malpositions. Eligible women were randomly assigned to either the control or study group. The control group received routine care during childbirth, while the study group received routine care and a childbirth-empowering educational intervention delivered by midwives. Primary outcomes assessed were childbirth experience and patient perceptions of patient-empowering nurse behaviors in pregnant women. Secondary outcomes included pregnancy outcomes, delivery support and control, maternal coping behavior during delivery, maternal participation in delivery decisions, and perception of empowerment. Results A total of 137 pregnant women were enrolled, with 69 and 68 in the control and study groups, respectively. The study group showed significantly higher levels of childbirth experience and reported better patient perceptions of patient-empowering nurse behaviors than the control group. Additionally, the study group demonstrated higher levels of delivery support and control, maternal coping behavior, and specific aspects of perceived participation and patient perception of empowerment compared to the control group. There were no statistically significant differences in pregnancy outcomes between the two groups. Conclusion The childbirth empowering educational intervention effectively improved the childbirth experience and empowerment of women with fetal occiput posterior and occiput transverse malpositions. However, further studies are required to investigate its impact on pregnancy outcomes. Trial registration The study protocol was approved by the hospital ethics committee (approval number:2020140A01) and registered at the Chinese Clinical Trial Registry (registration number: ChiCTR2300070915; date of first registration: 26/04/2023).